SEG Technical Program Expanded Abstracts 2002 2002
DOI: 10.1190/1.1817006
|View full text |Cite
|
Sign up to set email alerts
|

Repeated seismic surveys from the Norwegian Sea using new streamer technology

Abstract: Seismic reservoir monitoring has considerable unrealised potential if higher repeatability can be obtained. Today's towed streamer systems impose basic limitations on repeatability, as streamer feather is difficult to repeat and tow noise must be kept low. New streamer technology allows for horizontal steering of the streamers, which makes repeated streamer positions possible.During the 2001 summer season, time-lapse data were acquired over three producing fields in the Norwegian Sea using the new technology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…However, it is generally acknowledged ͑e.g., Ebrom et al, 1997;Calvert et al, 2002Calvert et al, , 2004Curtis et al, 2002;Eiken et al, 2002;Kragh and Christie, 2002͒ that the nonrepeatability effect resulting from mispositioning source-receiver locations in the repeated survey can be more significant than the production-induced 4D seismic signal.…”
Section: Effect Of Mispositioning On Traveltime Shift and Reflectivitmentioning
confidence: 99%
“…However, it is generally acknowledged ͑e.g., Ebrom et al, 1997;Calvert et al, 2002Calvert et al, , 2004Curtis et al, 2002;Eiken et al, 2002;Kragh and Christie, 2002͒ that the nonrepeatability effect resulting from mispositioning source-receiver locations in the repeated survey can be more significant than the production-induced 4D seismic signal.…”
Section: Effect Of Mispositioning On Traveltime Shift and Reflectivitmentioning
confidence: 99%
“…In this example, only Time-lapse changes between 2001 and 2003 will be considered. In order to reduce uncertainty related to Time-lapse seismic monitoring, the Qmarine technology from WesternGeco was used in the monitor surveys (Eiken et al, 2002).…”
Section: Time-lapse Seismic Acquisition and Processingmentioning
confidence: 99%
“…Harris and Adler (1999) investigated how the quality of the seismic data affects the accuracy of estimates of seismic variations in time‐shifts, phase rotation or amplitude variation between time‐lapse seismic data sets. Eiken et al . (2002) showed that repeated streamer positions were possible with new streamer technology that allowed for horizontal steering of the streamers.…”
Section: Introductionmentioning
confidence: 99%